1993
DOI: 10.1001/archinte.1993.00410030063009
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Nephropathy Associated With Hyperuricemia and Gout

Abstract: Increased serum urate concentrations in hereditary nephropathy associated with hyperuricemia and gout are due to severe impairment of uric acid excretion. Hyperuricemia does not appear, however, to be of pathogenetic relevance and may be a consequence of a primary disruption of renal hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
7

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 44 publications
0
15
0
7
Order By: Relevance
“…Renal excretion of uric acid is commonly involved in the development of gout, hyperuricemia, and nephropathy [1, 2]. The kidney filters freely circulating uric acid, accounting for ~70% of total uric acid excretion from the body [3].…”
Section: Introductionmentioning
confidence: 99%
“…Renal excretion of uric acid is commonly involved in the development of gout, hyperuricemia, and nephropathy [1, 2]. The kidney filters freely circulating uric acid, accounting for ~70% of total uric acid excretion from the body [3].…”
Section: Introductionmentioning
confidence: 99%
“…Duncan and Dixon [1]first reported a family with above condition in 1960, and Moro et al [2]called it ‘familial juvenile gouty nephropathy’ (FJGN). The pathogenesis of the renal disease is still unknown; however, the histological findings in kidney show nonspecific tubulointerstitial nephropathy with insignificant deposition of urate [3, 4, 5]. Correction of hyperuricemia with allopurinol is reported to ameliorate the progression of renal damage [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that urate secretion in these patients is unimpaired, the only explanation for low urate excretion is increased postsecretory reabsorption. This is unlikely to be a consequence of disturbed renal hemodynamics, as has been suggested [7]. Impaired renal perfusion or hypovolemia stimulate renal urate reabsorption, but usually do not cause gout or renal damage.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that treatment with allopurinol, an inhibitor of xanthine oxidase, slows progression of chronic renal failure [8]. Others, however, did not find a protective effect of allopurinol [7]. In general, FJGN patients seem to progress rather rapidly towards end-stage renal failure despite treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation